Corrosion and wear behaviour of alumina coatings obtained by various methods - Lampke, Т.; Meyer, D.; Alisch, G.; Wielage, B.; Pokhmurska, H.; Klapkiv, M.; Student, M. (Фізико-хімічна механіка матеріалів, 2010)
Alumina coatings are widely used in a range of industrial applications to improve corrosion protection, wear and erosion resistance and thermal insulation of metallic surfaces. From various efficient and adjustable processes refined alumina surfaces with long-term use are obtained. It can be seen that cost-efficient arc-sprayed Al coatings post-treated by plasma-electrolytic oxidation (PEO) form Al₂O₃-layers with remarkable corrosion protection, hardness, bonding strength and abrasion resistance as well as extended service time. The properties of these coatings are compared to alumina coatings obtained by flame spraying and atmospheric plasma spraying. Покриви на основі оксиду алюмінію широко використовують у промисловості для поліпшення корозійного захисту, зносо- та ерозійної тривкості, а також теплоізлояції металевих поверхонь. Різними методами отримано удосконалені покриви. Показано, що економічно ефективні алюмінієві покриви, сформовані методом електродугового розпилення, а потім оброблені плазмово-електролітичним оксидуванням, утворюють шари Al₂O₃ з високими антикорозійними характеристиками, твердістю, силою зчеплення та абразивною тривкістю і продовженим ресурсом роботи. Порівняно їх властивості з покривами на основі оксиду алюмінію, одержаними методами полуменевого та атмосферного плазмового розпилення. Покрытия на основе оксида алюминия часто применяют в промышленности для улучшения коррозионной защиты, износо- и эрозионной стойкости, а также теплоизлояции металлических поверхностей. Различнымы методами получены усовершенствованные покрытия. Показано, что экономически эффективные алюминиевые покрытия, сформированные методом электродугового распыления, а потом обработаные плазменно-электролитическим оксидированием, образуют слои Al₂O₃ с высокими антикоррозионными характеристиками, твердостью, силой сцепления, абразивной стойкостью и длительным ресурсом работы. Сравнены их свойства с покрытиями на основе оксида алюминия, полученными методами пламенного и атмосферного плазменного распыления.